2011
DOI: 10.1161/circulationaha.111.027375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perivascular Adipose Tissue–Derived Methyl Palmitate in Vascular Tone Regulation and Pathogenesis of Hypertension

Abstract: Background-Perivascular adipose tissue (PVAT)-derived relaxing factor (PVATRF) significantly regulates vascular tone. Its chemical nature remains unknown. We determined whether palmitic acid methyl ester (PAME) was the PVATRF and whether its release and/or vasorelaxing activity decreased in hypertension. Methods and Results-Using superfusion bioassay cascade technique, tissue bath myography, and gas chromatography/mass spectrometry, we determined PVATRF and PAME release from aortic PVAT preparations of Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
139
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 40 publications
3
139
3
3
Order By: Relevance
“…Lin et al (2008) first reported that PAME released from SCG (the largest cervical ganglion in the sympathetic tract (Lee et al, 2011a(Lee et al, , 2011bLee et al, 2012;Wu et al, 2014)) is a novel vasodilator (Lin et al, 2008). Exogenous application of PAME directly onto the rabbit or rat thoracic aorta induced vasodilation in a concentration-dependent manner (Lin et al, 2008;Lee et al, 2010;Lee et al, 2011c). The EC 50 value (the concentration that induces 50% of the maximum relaxation) for PAME-elicited aortic vasodilation is 0.19 nM which is at least 178 times (vs. 34.8 nM) lower than that of sodium nitroprusside (NO donor)-induced vasodilation (BrizzolaraGourdie and Webb, 1997; Lin et al, 2008) indicating that PAME is a potent vasodilator.…”
Section: Fatty Acidsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lin et al (2008) first reported that PAME released from SCG (the largest cervical ganglion in the sympathetic tract (Lee et al, 2011a(Lee et al, , 2011bLee et al, 2012;Wu et al, 2014)) is a novel vasodilator (Lin et al, 2008). Exogenous application of PAME directly onto the rabbit or rat thoracic aorta induced vasodilation in a concentration-dependent manner (Lin et al, 2008;Lee et al, 2010;Lee et al, 2011c). The EC 50 value (the concentration that induces 50% of the maximum relaxation) for PAME-elicited aortic vasodilation is 0.19 nM which is at least 178 times (vs. 34.8 nM) lower than that of sodium nitroprusside (NO donor)-induced vasodilation (BrizzolaraGourdie and Webb, 1997; Lin et al, 2008) indicating that PAME is a potent vasodilator.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…However, it has also been shown that PAME spontaneously released from the retina is described as the retinaderived relaxing factor (Lee et al, 2010) which induces potent vasodilation in the pre-contracted rat aorta suggesting an important role in retinal circulation (Lee et al, 2010). In addition, PAME is also released from perivascular adipose tissue (PVAT), which has been reported to be PVAT-derived relaxing factor (Lee et al, 2011c) regulating systemic blood pressure. It is interesting to note that the reduction of PAME released from PVAT can be observed in genetic hypertensive rats (Lee et al, 2011c).…”
Section: Vascular Reactivitymentioning
confidence: 99%
See 3 more Smart Citations